Investigating inter-turn fault in transformer using TTR and FRA - Abdulrazzaq Al-Iedani, Ali Salman (2019)
Transformers are one of the significant elements in the power system network. The Transformer function is to step up and down the voltages. When the transformer operating in high load, it exposes to failures. There are various transformer failures which could have a serious effect on the transformer efficiency. For example, winding deformation, tap changer damage, and short turns (inter-turn fault). The transformer inter-turns fault reduces the number of turns in the winding. To detect inter-turn fault, the transformer turn ratio test is the basic method used. On the other hand, frequency response analysis has been recognized to monitor the mechanical condition of the transformer winding. The frequency response analysis method can be conducted in four measurement connection. They are end to end open circuit test, end to end short circuit test, capacitive inter-winding, and inductive inter-winding. The inductive inter-winding low-frequency region is determined by the transformer turn ratio. This statement was mentioned in CIGRE A2.26. However, there are not approved studies on this issue. This study investigates the transformer inter-turn fault using transformer turn ratio test and frequency response analysis. In addition, this study performs various of statistical indicators on the FRA results. The statistical indicators are used to detect the variation between the normal and inter-turn fault responses. Also, this study proposes statistical indicators limits. After that compare the FRA and TTR results and check if the turn ratio results can be obtained using FRA inductive inter-winding test. Findings that FRA inductive inter-winding test can detect inter-turn fault. This can be determined by the absolute sum logarithmic error (ASLE), mean square error (MSE), and standard deviation (SD). Also, there are indicator limits has been proposed for ALSE and SD. This study finding helps to use the frequency response analysis method to replace the conventional turn ratio test.